PENGARUH CREATIVE PROBLEM SOLVING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV DI SD INPRES OEPURA 1 - Treesly Y. N. Adoe; Tunggal Karsa Tri Mandala Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research discusses the Influence of Creative problem solving Assisted by Audio-Visual Media on the Learning Outcomes of Fourth Grade Students at SD Inpres Oepura 1. This research is motivated by the fact that teaching concepts and theories are still limited to a one-way approach and have not yet centered on students, educators have not maximized the use of engaging and innovative media or models in the learning process, and the low learning outcomes of students.  The research used is pre experimental designs with a One-Group Pretest-Posttest Design. The research sample in pre experimental designs is first given a pretest to determine the initial abilities of the students before the treatment is given. Subsequently, the sample is given a posttest. (posttest). The data collection method used a pretest-posttest written test. The analysis technique used a t-test. Based on the analysis results, the average pretest score was 61.25 and the average posttest score was 82.29. The results of the pretest and posttest calculations show a sig. (2-tailed) value of 0.001. Based on the calculations, the obtained sig. (2-tailed) value <0.001 ≤ 0.05, thus Ho is rejected and Ha is accepted. Thus, it can be concluded that there is a difference in the average learning outcomes of students before and after the treatment was given. This confirms the research hypothesis that there is an influence of the creative problem-solving learning model assisted by audiovisual media on the learning outcomes of fourth-grade students.